1990
DOI: 10.1039/c39900000082
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise two-proton transfer within the formamidine dimer. A theoretical study using Ab initio calculations

Abstract: Ab initio calculations at the VDZ and VDZ + P levels of theory of the two-proton transfer reaction within an isolated formamidine dimer give transition states with low symmetry, and with 6-31G" basis sets indicate stepwise two-proton transfers even in the absence of solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The difference in energy between R and I (Δ E ) and the barrier heights (Δ E* ) are listed in Table . They depend very much on the levels of quantum mechanical calculations and the inclusion of electron correlation. , The Δ E values at the HF/6-31+G(d,p) and B3LYP/6-31+G(d,p) levels are 22.85 and 19.08 kcal mol -1 , respectively. The Δ E* values at the HF/6-31+G(d,p), B3LYP/6-31+G(d,p), and MP2(full)/6-31G(d,p) levels are 32.62, 22.52, and 24.93 kcal mol -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in energy between R and I (Δ E ) and the barrier heights (Δ E* ) are listed in Table . They depend very much on the levels of quantum mechanical calculations and the inclusion of electron correlation. , The Δ E values at the HF/6-31+G(d,p) and B3LYP/6-31+G(d,p) levels are 22.85 and 19.08 kcal mol -1 , respectively. The Δ E* values at the HF/6-31+G(d,p), B3LYP/6-31+G(d,p), and MP2(full)/6-31G(d,p) levels are 32.62, 22.52, and 24.93 kcal mol -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the light mass of the transferred atom, the importance of tunneling in proton transfer reactions has been discussed for many years . Recently many theoretical studies with ab initio quantum chemical methods at various levels have been carried out to predict the structures of hydrogen-bonded dimers and the potential energy surfaces (PESs) for various double proton transfer processes. It has been shown that the height and shape of the PES depend strongly on the theoretical level of calculation, the size of the basis set, and the inclusion of correlation energy. ,, ,15 Since most of the earlier studies have focused on the geometrical change on dimerization and the energetic stabilization due to the hydrogen bonds in the dimer, the dynamic features of the double proton transfer, such as tunneling and the effect of isotopic substitution, are not yet very well understood. To study the dynamics of such systems, detailed information about the potential energy surface near the TS and the critical configuration is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serving as a model for hydrogen transfer reactions in bases of nucleic acids, formamidine has been extensively studied theoretically since it also forms homodimers and hydrogen bonds with water. Intramolecular and intermolecular hydrogen transfers have been studied theoretically for various formamidine systems. ,, Proton transfers in formamidine dimer can also be considered a prototype of multiproton transfer. They can also provide information about hydrogen bonding, as well as the proton relay mechanism in enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Forming a homodimer can also facilitate the tautomerization reaction, and therefore we have studied the double proton transfer in the dimer-assisted as well as the water-assisted tautomerization in the gas phase and in solution. Since electron correlation plays an important role in determining the characteristics of the PES for the proton transfer reaction in the gas phase, ,, it is necessary to consider the correlation effect in solution too. The density functional theory has been successfully applied to the proton transfer reactions and it agrees well with other methods including high-level electron correlation.…”
Section: Introductionmentioning
confidence: 99%
“…At this level the two hydrons are transferred concertedly and synchrono~sly.~ It was later shown that with more extended basis sets the minimum energy path for the two-hydron transfer in this system corresponds to a stepwise mechanism. 5 In the present communication we present some data on the formic acid dimer system. This system shows a concerted and synchronous transfer of the two hydrons at all computational levels that have been used.…”
mentioning
confidence: 94%